Practices in performing lumbar puncture procedure in the Children Welfare Teaching Hospital / Baghdad - saadi, nebal wael; Mohammed, Dhulfiqar A.; Kareem, Yousif W.; Jawad, Abdullah K. (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Lumbar puncture is a procedure that is frequently performed in the pediatric practice. Objective: To review some (patient, provider and technique- related) characteristics of lumbar puncture performed at the Children Welfare Teaching Hospital, Baghdad / Iraq. Methods: A descriptive cross-sectional study was conducted in the period from April to September, 2017. A self-prepared questionnaire was used to collect the data. It included 32 items, which were divided into three sections: Residents doctors’ information (3 items), patient’s information (2 items) and procedure’s information (27 items). Results: The total number of performed procedures was 103, of which 51 (49.5%) were performed in the oncology ward. About half (50, 48.6%) of the patients were preschool-aged. Lumbar puncture was indicated for diagnostic purposes in 52(50.5%) cases. Nearly two thirds (67, 65.9%) of the procedures was performed by senior residents (3rd/4th Board residents). A written consent was obtained in only one case, the couch sheet were not renewed in 92 (93.9%) cases, a drape were not used in 92 (93.9%) cases, sitting upright position was assumed in 90 (91.8%) cases, gloves were worn by the doctor in all cases, anesthesia was used in 47 (48%) cases, antiseptics were used in 97 (99%) cases ,one holder was noted in 93 (94.8%) cases ,SpinocanQuincke and 22 Gage needle type was used in 98 (100%) cases, one entry attempt per procedure was reported in 79 (80.6%) cases and no documentation in the patients’ notes was reported in any of the procedures. Conclusion: Lumbar puncture load was found in the oncology ward both for the patients and the residents. Safety was considered but was suboptimal in all wards.